Analisis Kekuasaan Sultan Merangkap Gubernur Pada Pemerintahah Daerah Istimewa Yogyakarta - Muhammad Yusya Rahmansyah; Wiwi Widiastuti; Hendra Gunawan (Epistemik: Indonesian Journal of Social and Political Science, 2021)
This study aims to analyze and find out what the mechanisms of democracy, especially in practice, are in the Special Region of Yogyakarta. Because Yogyakarta is an area that has specialties other than in terms of culture and customs, Yogyakarta also has specialties in terms of regional power. Where through a law that has been passed stipulates that the province of Yogyakarta is led by a Sultan who includes the duties as regional governor. The Special Region of Yogyakarta has the privilege of running its government, where the kingdom still has a role in formal government. Using a phenomenological analysis approach By using a phenomenological analysis and approach, the power of the sultan and governor can be analyzed into a democratic phenomenon that occurs in Indonesia. In this way, it is hoped that a reality related to power, democracy and culture will be revealed with the theory of democracy, the concept of Javanese power, and authority. Using descriptive analysis methods with in-depth interviews and observation techniques and with data validation using source triangulation to recheck the data so that the data obtained are reliable facts.